Preparation method of crystallizer copper plate surface coating
The Ni-W-TiB2-Cu composite coating addresses bonding and hardness issues in crystallizer copper plates by forming a solid solution phase, thereby improving durability and service life.
Patent Information
- Application Number
- CN202411325626.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
AI Technical Summary
Existing surface coatings for crystallizer copper plates in continuous casting processes suffer from poor bonding, hardness, and wear resistance, leading to reduced service life and production issues.
A surface coating composed of a Ni-W-TiB2-Cu composite material is prepared by ball-milling nickel and tungsten powders, adding titanium boride and copper, followed by sintering and spraying onto the crystallizer copper plate substrate, forming a solid solution phase with enhanced bonding and hardness.
The Ni-W-TiB2-Cu composite coating significantly improves bonding strength and hardness, extending the service life of the crystallizer copper plate and enhancing its durability.
Smart Images

Figure CN119243075A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface treatment of a crystallizer copper plate, and in particular relates to a method for preparing a surface coating of a crystallizer copper plate. Background Art
[0002] In the continuous casting production process, the crystallizer is the core component of continuous casting and is called the heart of the continuous casting machine. As the key equipment for forming the primary shell of the continuous casting billet, the crystallizer is the first step to realize the transformation of molten steel from liquid to solid. In the crystallizer, liquid molten steel continuously flows into the crystallizer, and a weak primary shell is formed at the meniscus under the strong cooling of the crystallizer. As the billet moves downward, the surface temperature of the billet shell continues to decrease, and the billet shell gradually thickens. Therefore, the life and durability of the crystallizer directly affect the continuous casting production efficiency. Problems such as cracks, oxidation, and recrystallization that occur in the crystallizer copper plate during the production process will cause cracks and scarring on the surface of the billet in mild cases, and steel leakage in severe cases, which plays a vital role in product quality and smooth production.
[0003] The development of crystallizer copper plate coating has successively gone through Cr coating, Ni coating, Ni-Fe coating, Ni-Co (Co-Ni) coating, among which Co-Ni alloy coating has high high temperature hardness, good thermal stability, strong electrochemical corrosion resistance, and is an ideal coating for crystallizer copper plate, but Co has high cost, high coating stress when hardness is high, and poor heat resistance. Therefore, in recent years, researchers have continuously applied new processes and new materials to develop different coatings to further improve the surface properties of crystallizer copper plate. For example, patent CN108070813A discloses a method for preparing a corrosion-resistant Cr3C2-NiCr-aluminum-silicon composite siloxane composite coating on the surface of a crystallizer copper plate, and adopts supersonic flame spraying and immersion pulling method to synthesize hundreds of microns of Cr3C2-NiCr layer and tens of microns of aluminum-silicon composite siloxane coating on the surface of the crystallizer copper plate in sequence, and the composite coating has good corrosion resistance. However, according to the patents that have been reported, although the performance of the coated crystallizer copper plate is slightly improved compared with the past, its service life is still not high. The main reason is that the coating is poor in bonding, hardness, and wear resistance. Therefore, the performance of the surface coating of the crystallizer copper plate needs to be further improved. Summary of the invention
[0004] The technical problem to be solved by the present invention is to address the deficiencies in the prior art and to provide a method for preparing a surface coating of a crystallizer copper plate. The surface coating is a Ni-W-TiB2-Cu composite material, in which W and TiB2 are mutually dissolved in a solid solution to form a hard phase, which is wrapped by an indeterminate phase formed by Cu and Ni. Not only does it achieve higher hardness and wear resistance, but the surface coating also has good bonding inside and between the surface coating and the crystallizer copper plate substrate, thereby greatly extending the service life of the crystallizer copper plate.
[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a method for preparing a surface coating of a crystallizer copper plate, comprising the following steps:
[0006] 1) ball-milling nickel powder and tungsten powder to obtain a first mixed powder;
[0007] 2) adding titanium boride powder and copper powder to the first mixed powder and stirring evenly to obtain a second mixed powder;
[0008] 3) sintering the second mixed powder by vacuum hot pressing or vacuum hot isostatic pressing, and then crushing the sintered product to obtain a coating composite powder;
[0009] 4) After pre-treating the surface of the crystallizer copper plate substrate, the coating composite powder is sprayed onto the surface of the crystallizer copper plate substrate by supersonic flame spraying or plasma spraying to form a surface coating.
[0010] In the above scheme, the purity of the nickel powder is greater than 99% and the particle size is 3 to 10 μm.
[0011] In the above solution, the purity of the tungsten powder is greater than 99% and the particle size is 1 to 10 μm.
[0012] In the above scheme, the mass ratio of the nickel powder to the tungsten powder is (3-4):1.
[0013] Preferably, the mass ratio of the nickel powder to the tungsten powder is (3.5-4):1.
[0014] In the above scheme, the ball milling adopts a planetary ball mill equipped with a stainless steel vacuum ball milling tank and a high-hardness metal ball mill for vacuum ball milling. The vacuum degree is 100-10Pa, the ball milling speed is 300-400r / min, and the ball milling time is 18-36h.
[0015] In the above solution, the particle size of the first mixed powder is 1 to 8 μm.
[0016] In the above solution, the purity of the titanium boride powder is greater than 99% and the particle size is less than 1 μm.
[0017] In the above solution, the mass of the titanium boride powder is 5-8% of the mass of the first mixed powder.
[0018] Preferably, the mass of the titanium boride powder is 5-6% of the mass of the first mixed powder.
[0019] In the above solution, the purity of the copper powder is greater than 99% and the particle size is less than 1 μm.
[0020] In the above solution, the mass of the copper powder is 1-5% of the mass of the first mixed powder.
[0021] Preferably, the mass of the copper powder is 2-4% of the mass of the first mixed powder.
[0022] In the above scheme, the vacuum degree of the vacuum hot pressing sintering or vacuum hot isostatic pressing sintering is 10 -3 ~10 -2 Pa, the sintering temperature is 1300-1450℃, the pressure is 20-40MPa, and the holding time is 0.5-2h.
[0023] Preferably, the vacuum degree of the vacuum hot isostatic pressing sintering is 3×10 -3 ~6×10 -3 Pa, the sintering temperature is 1400-1450℃, the pressure is 25-35MPa, and the holding time is 1-2h.
[0024] In the above solution, the particle size of the coating composite powder is less than 5 μm.
[0025] In the above scheme, the crystallizer copper plate substrate is Ag-Cu alloy or Cu-Cr-Zr alloy.
[0026] Furthermore, when the crystallizer copper plate substrate is an Ag-Cu alloy, its chemical composition by mass percentage includes: Cu>99.5%, Ag 0.05% to 0.1%, and the rest are unavoidable impurities.
[0027] Furthermore, when the copper plate substrate of the crystallizer is a Cu-Cr-Zr alloy, its chemical composition by mass percentage includes: Cu>98%, Cr 0.5-1.5%, Zr 0.01-0.3%, and the rest are unavoidable impurities.
[0028] In the above scheme, the pretreatment first uses a NaOH solution with a mass fraction of 25-40% for surface cleaning, and then uses a H2SO4 solution with a mass fraction of 3-8% for surface treatment.
[0029] In the above solution, the thickness of the surface coating is 0.5 to 2 mm.
[0030] In the above scheme, the density of the surface coating is greater than 99.7%, the hardness HV10 is 1300-1500, and the bonding strength between the surface coating and the crystallizer copper plate substrate is 290-400 MPa.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention prepares the surface coating of the crystallizer copper plate in a manner that nano-TiB2 forms a solid solution phase between crystals. Ni and W serve as solid solution promoters. Through the solid solution effect of TiB2, W atoms chemically react with TiB2 lattices at grain boundaries to generate metal diboride solid solutions such as W2NiB2 and (Ti, W)B2 and other composite bonding phases, which can not only enhance the bonding strength between coating crystals, but also greatly improve the hardness and wear resistance of the coating. At the same time, Cu is further added, and the W-TiB2 generated by the reaction is wrapped by Cu and Ni powder as a hard phase. After spraying, Ni and Cu in the coating form a transition layer with the copper plate substrate, and the transition layer can form a good bond between the coating and the copper plate substrate. In addition, Cu and W form an amorphous bonding interface at high temperature, which not only enhances the bonding strength between the coating and the copper plate substrate, but also strengthens the bonding inside the coating, further improving the hardness and wear resistance of the coating; thereby greatly extending the service life of the crystallizer copper plate. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the cross-sectional microstructure of the surface coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0035] In the following examples, the density of the surface coating was tested using the "GB / T 25995-2010 Fine Ceramics Density and Apparent Porosity Test Method"; the hardness of the surface coating was tested using the "GB / T 16534-2009 Fine Ceramics Room Temperature Hardness Test Method"; and the bonding strength between the surface coating and the crystallizer copper plate substrate was tested using the "GB / T 6569-2006 Fine Ceramics Bending Strength Test Method".
[0036] Example 1
[0037] A method for preparing a surface coating of a crystallizer copper plate comprises the following steps:
[0038] 1) Mixing metal nickel powder and metal tungsten powder in a mass ratio of 4:1 into a stainless steel vacuum ball mill, adding a high-hardness metal ball mill, evacuating to a vacuum degree of 20 Pa, and using a planetary ball mill at a speed of 350 r / min for 24 h to obtain a first mixed powder with a particle size of 2 to 5 μm;
[0039] 2) adding 6% by weight of nano titanium boride powder and 2% by weight of metal copper powder to the first mixed powder, and stirring the mixture evenly with a vertical barrel mixer to obtain a second mixed powder;
[0040] 3) The second mixed powder is subjected to vacuum hot pressing sintering with a vacuum degree of 4×10 -3 Pa, sintering temperature is 1350°C, hot pressing pressure is 30MPa, holding time is 1h, the sintered product is crushed to obtain a coating composite powder with a particle size of 2 to 4μm;
[0041] 4) The surface of the crystallizer copper plate substrate is first cleaned with a 30% by mass NaOH solution, and then surface treated with a 3% by mass H2SO4 solution. Finally, the coating composite powder is sprayed onto the surface of the crystallizer copper plate substrate by supersonic flame spraying to form a surface coating with a thickness of 1.5 mm.
[0042] In this embodiment, the purity of the metal nickel powder is 99.7%, and the particle size is 5 μm; the purity of the metal tungsten powder is 99.8%, and the particle size is 3 μm; the purity of the metal copper powder is 99.7%, and the particle size is 0.5 μm; the purity of the nano-titanium boride powder is 99.5%, and the particle size is 0.3 μm; the crystallizer copper plate substrate is Ag-Cu alloy, and its chemical composition by mass percentage includes: Cu 99.6%, Ag 0.08%, and the rest are unavoidable impurities.
[0043] Figure 1 This is the cross-sectional microstructure of the surface coating prepared in this embodiment. As can be seen from the figure, W and TiB2 are mutually dissolved (black area) and are wrapped by the amorphous phase formed by Ni and Cu (gray area), which illustrates that the Ni-W-TiB2-Cu interface solid solution effect is good.
[0044] According to the test, the density of the surface coating of the crystallizer copper plate is 99.8%, the hardness HV10 reaches 1350, the bonding strength between the surface coating and the substrate is 325MPa, and the actual single steel passing capacity is 72,000 tons / set.
[0045] Example 2
[0046] A method for preparing a surface coating of a crystallizer copper plate comprises the following steps:
[0047] 1) Mix metal nickel powder and metal tungsten powder in a mass ratio of 3.5:1 and put them into a stainless steel vacuum ball mill, add a high-hardness metal ball mill, evacuate to a vacuum degree of 25 Pa, and use a planetary ball mill to ball mill for 30 hours at a speed of 380 r / min to obtain a first mixed powder with a particle size of 3 to 6 μm;
[0048] 2) adding 5% by weight of nano titanium boride powder and 1.5% by weight of metal copper powder to the first mixed powder, and stirring the mixture evenly with a vertical barrel mixer to obtain a second mixed powder;
[0049] 3) The second mixed powder is subjected to vacuum hot pressing sintering with a vacuum degree of 3×10 -3Pa, sintering temperature is 1400℃, hot pressing pressure is 25MPa, holding time is 1.5h, the sintered product is crushed to obtain coating composite powder with a particle size of about 3μm;
[0050] 4) The surface of the crystallizer copper plate substrate was first cleaned with a 35% by mass NaOH solution, and then surface treated with a 5% by mass H2SO4 solution. Finally, the coating composite powder was sprayed onto the surface of the crystallizer copper plate substrate by supersonic flame spraying to form a surface coating with a thickness of 1.8 mm.
[0051] In this embodiment, the purity of the metal nickel powder is 99.8%, and the particle size is 3.5μm; the purity of the metal tungsten powder is 99.8%, and the particle size is 2.5μm; the purity of the metal copper powder is 99.8%, and the particle size is 0.5μm; the purity of the nano-titanium boride powder is 99.5%, and the particle size is 0.2μm; the crystallizer copper plate substrate is Ag-Cu alloy, and its chemical composition by mass percentage includes: Cu 99.7%, Ag 0.08%, and the rest are unavoidable impurities.
[0052] According to the test, the density of the surface coating of the crystallizer copper plate is 99.8%, the hardness HV10 reaches 1380, the bonding strength between the surface coating and the substrate is 350MPa, and the actual single steel passing capacity is 82,000 tons / set.
[0053] Example 3
[0054] A method for preparing a surface coating of a crystallizer copper plate comprises the following steps:
[0055] 1) Mixing metal nickel powder and metal tungsten powder in a mass ratio of 3:1 into a stainless steel vacuum ball mill, adding a high-hardness metal ball mill, evacuating to a vacuum degree of 40 Pa, and using a planetary ball mill at a speed of 400 r / min for 36 hours to obtain a first mixed powder with a particle size of 2 to 6 μm;
[0056] 2) adding 5.5% by weight of nano titanium boride powder and 2% by weight of metal copper powder to the first mixed powder, and stirring the mixture evenly with a vertical barrel mixer to obtain a second mixed powder;
[0057] 3) The second mixed powder is subjected to vacuum hot isostatic pressing sintering with a vacuum degree of 5×10 -3 Pa, sintering temperature is 1410℃, pressure is 35MPa, holding time is 2h, the sintered product is crushed to obtain coating composite powder with a particle size of about 4.5μm;
[0058] 4) The surface of the crystallizer copper plate substrate is first cleaned with a 35% by mass NaOH solution, and then surface treated with a 6% by mass H2SO4 solution. Finally, the coating composite powder is sprayed onto the surface of the crystallizer copper plate substrate by plasma spraying to form a surface coating with a thickness of 1.5 mm.
[0059] In this embodiment, the purity of the metal nickel powder is 99.6%, and the particle size is 6μm; the purity of the metal tungsten powder is 99.7%, and the particle size is 5μm; the purity of the metal copper powder is 99.7%, and the particle size is 0.3μm; the purity of the nano-titanium boride powder is 99.7%, and the particle size is 0.5μm; the crystallizer copper plate substrate is a Cu-Cr-Zr alloy, and its chemical composition by mass percentage includes: Cu 98.5%, Cr 0.8%, Zr0.1%, and the rest are unavoidable impurities.
[0060] According to the test, the density of the surface coating of the crystallizer copper plate is 99.9%, the hardness HV10 reaches 1450, the bonding strength between the surface coating and the substrate is 380MPa, and the actual single steel passing capacity is 91,000 tons / set.
[0061] Example 4
[0062] A method for preparing a surface coating of a crystallizer copper plate comprises the following steps:
[0063] 1) Mix metal nickel powder and metal tungsten powder in a mass ratio of 4:1 and put them into a stainless steel vacuum ball mill, add a high-hardness metal ball mill, evacuate to a vacuum degree of 50 Pa, and use a planetary ball mill to mill at a speed of 380 r / min for 32 hours to obtain a first mixed powder with a particle size of 3 to 7 μm;
[0064] 2) adding 7% by weight of nano titanium boride powder and 3% by weight of metal copper powder to the first mixed powder, and stirring the mixture evenly with a vertical barrel mixer to obtain a second mixed powder;
[0065] 3) The second mixed powder is subjected to vacuum hot isostatic pressing sintering with a vacuum degree of 6×10 -3 Pa, sintering temperature is 1450℃, pressure is 38MPa, holding time is 2h, the sintered product is crushed to obtain coating composite powder with a particle size of about 4.5μm;
[0066] 4) The surface of the crystallizer copper plate substrate is first cleaned with a 38% by mass NaOH solution, and then surface treated with a 5% by mass H2SO4 solution. Finally, the coating composite powder is sprayed onto the surface of the crystallizer copper plate substrate by plasma spraying to form a surface coating with a thickness of 1.8 mm.
[0067] In this embodiment, the purity of the metal nickel powder is 99.8%, and the particle size is 8μm; the purity of the metal tungsten powder is 99.8%, and the particle size is 7μm; the purity of the metal copper powder is 99.5%, and the particle size is 0.5μm; the purity of the nano-titanium boride powder is 99.6%, and the particle size is 0.3μm; the crystallizer copper plate substrate is a Cu-Cr-Zr alloy, and its chemical composition by mass percentage includes: Cu 98.5%, Cr 0.6%, Zr0.05%, and the rest are unavoidable impurities.
[0068] According to the test, the density of the surface coating of the crystallizer copper plate is 99.9%, the hardness HV10 reaches 1490, the bonding strength between the surface coating and the substrate is 390MPa, and the actual single steel passing capacity is 95,000 tons / set.
[0069] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A method for preparing a surface coating of a crystallizer copper plate, characterized in that: The following steps are involved: 1) ball-milling nickel powder and tungsten powder to obtain a first mixed powder; 2) adding titanium boride powder and copper powder to the first mixed powder and stirring evenly to obtain a second mixed powder; 3) sintering the second mixed powder by vacuum hot pressing or vacuum hot isostatic pressing, and then crushing the sintered product to obtain a coating composite powder; 4) After pre-treating the surface of the crystallizer copper plate substrate, the coating composite powder is sprayed onto the surface of the crystallizer copper plate substrate by supersonic flame spraying or plasma spraying to form a surface coating.
2. The method for preparing a surface coating of a crystallizer copper plate according to claim 1, characterized in that: The mass ratio of the nickel powder to the tungsten powder is (3-4):1; the mass of the titanium boride powder is 5-8% of the mass of the first mixed powder; and the mass of the copper powder is 1-5% of the mass of the first mixed powder.
3. The method for preparing a surface coating of a crystallizer copper plate according to claim 1, characterized in that: The mass ratio of the nickel powder to the tungsten powder is (3.5-4):1; the mass of the titanium boride powder is 5-6% of the mass of the first mixed powder; and the mass of the copper powder is 2-4% of the mass of the first mixed powder.
4. The method for preparing a surface coating of a crystallizer copper plate according to claim 1, characterized in that: The vacuum degree of the vacuum hot pressing sintering or vacuum hot isostatic pressing sintering is 10 -3 ~10 -2 Pa, the sintering temperature is 1300-1450°C, the pressure is 20-40MPa, and the holding time is 0.5-2h.
5. The method for preparing a surface coating of a crystallizer copper plate according to claim 1, characterized in that: The vacuum degree of the vacuum hot pressing sintering or vacuum hot isostatic pressing sintering is 3×10 -3 ~6×10 -3 Pa, the sintering temperature is 1400-1450℃, the pressure is 25-35MPa, and the holding time is 1-2h.
6. The method for preparing a surface coating of a crystallizer copper plate according to claim 1, characterized in that: In step 1), the ball milling is performed by a planetary ball mill under vacuum, the vacuum degree is 100-10Pa, the ball milling speed is 300-400r / min, and the ball milling time is 18-36h; the particle size of the first mixed powder is 1-8μm.
7. The method for preparing a surface coating of a crystallizer copper plate according to claim 1, characterized in that: The particle size of the coating composite powder is less than 5 μm; the thickness of the surface coating is 0.5-2 mm, the density is greater than 99.7%, the hardness HV10 is 1300-1500, and the bonding strength between the surface coating and the crystallizer copper plate substrate is 290-400 MPa.
8. The method for preparing a surface coating of a crystallizer copper plate according to claim 1, characterized in that: The crystallizer copper plate substrate is Ag-Cu alloy or Cu-Cr-Zr alloy; when it is Ag-Cu alloy, its chemical composition includes by mass percentage: Cu>99.5%, Ag 0.05%-0.1%, and the rest are inevitable impurities; when it is Cu-Cr-Zr alloy, its chemical composition includes by mass percentage: Cu>98%, Cr 0.5-1.5%, Zr 0.01-0.3%, and the rest are inevitable impurities.
9. The method for preparing a surface coating of a crystallizer copper plate according to claim 1, characterized in that: The purity of the nickel powder is greater than 99%, and the particle size is 3-10 μm; the purity of the tungsten powder is greater than 99%, and the particle size is 1-10 μm; the purity of the titanium boride powder is greater than 99%, and the particle size is less than 1 μm; the purity of the copper powder is greater than 99%, and the particle size is less than 1 μm.
10. The method for preparing a surface coating of a crystallizer copper plate according to claim 1, characterized in that: The pretreatment first uses a NaOH solution with a mass fraction of 25-40% to clean the surface, and then uses a H2SO4 solution with a mass fraction of 3-8% to treat the surface.
Citation Information
Cited By
Powder for crystallizer copper plate coating
CN121874569A
TiB2-TiC-W composite ceramic with superhard fine-crystal core-shell structure as well as preparation method and application of TiB2-TiC-W composite ceramic
CN122102703A
An ultra-hard fine-grain core-shell structure TiB2-TiC-W composite ceramic and a preparation method and application thereof
CN122102703B